Clinical end points for drug treatment trials in BCR-ABL1-negative classic myeloproliferative neoplasms: consensus statements from European LeukemiaNET (ELN) and Internation Working Group-Myeloproliferative Neoplasms Research and Treatment (IWG-MRT) - Barosi, Giovanni; Hehlmann, Rüdiger; Reiter, Andreas (Leukemia, 2015)
The discovery of somatic mutations, primarily JAK2V617F and CALR, in classic BCR-ABL1-negative myeloproliferative neoplasms (MPNs) has generated interest in the development of molecularly targeted therapies, whose accurate assessment requires a standardized framework. A working group, comprised of members from European LeukemiaNet (ELN) and International Working Group for MPN Research and Treatment (IWG-MRT), prepared consensus-based recommendations regarding trial design, patient selection and definition of relevant end points. Accordingly, a response able to capture the long-term effect of the drug should be selected as the end point of phase II trials aimed at developing new drugs for MPNs. A time-to-event, such as overall survival, or progression-free survival or both, as co-primary end points, should measure efficacy in phase III studies. New drugs should be tested for preventing disease progression in myelofibrosis patients with early disease in randomized studies, and a time to event, such as progression-free or event-free survival should be the primary end point. Phase III trials aimed at preventing vascular events in polycythemia vera and essential thrombocythemia should be based on a selection of the target population based on new prognostic factors, including JAK2 mutation. In conclusion, we recommended a format for clinical trials in MPNs that facilitates communication between academic investigators, regulatory agencies and drug companies.